TAX COSTS AND CORPORATION DIVIDEND POLICY: Evidence from the 1986 U.S. Tax Reform Acts - Utama, Siddharta (Gadjah Mada International Journal of Business, 2003)
Scholes and Wolfson (1992) predict that following the 1986 TaxReform Act, the tax cost of the corporate form relative to that of the partnership form (the incremental tax cost) increased significantly. This study hypothesizes that since dividends represent a tax disadvantaged form of income relative to capital gains, then in response to an increase in incremental tax costs, corporations would decrease their dividend payout ratios. The response is expected to be stronger for corporations owned byshareholders with long investment horizons because the tax cost saved from decreasing dividend payout ratios is an increasing function of shareholdersâ investment horizon. The empirical tests support the hypothesis and show a negative relationship between the change in incremental tax costs and the change in dividend payout ratios for firms with long average investment horizons.